PERAMALAN PERUBAHAN PROFITABILITAS PERUSAHAAN MENGGUNAKAN PERUBAHAN ASSET TURNOVER DAN PROFIT MARGIN - Maharanie, Dhea Sinta; Suryani, Ani Wilujeng (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2023)
Financial analysis is an important component of a business because it enables forecasting of future performances. Return on net operating assets (RNOA) is commonly used measurement to forecast changes in company profitability. As such, the purpose of this study is to forecast profitability through the use of RNOA. The study was carried out on companies listed on the IDX30 from 2012 to 2018. Weighted least squared regression panel data is used to examine the effect of RNOA on company profitability forecast. The results show that ΔRNOA disaggregation has a positive effect on company profitability, whereas in RNOA, only profit margin (PM) that has a positive effect on profitability. These findings suggest the importance of improving the company's revenue management, which is useful in providing information about the company's future profitability.